Challenges of E-Examination Adoption and the Role of Block chain in Enhancing Security and Trust: A Field Study at the Faculty of Science, Gharyan– Libya - Howida Fathi Almalaoushi,; Hajir Saied Almshawit, (African Journal of Advanced Pure and Applied Sciences, 2025)
In recent years, higher education has witnessed a significant shift toward digital environments, with e-exams becoming an essential tool for academic assessment due to their speed, efficiency, and reduced administrative burdens. However, the adoption of e-exams in Libyan educational institutions, particularly at the Faculty of Science in Gharyan, still faces challenges stemming from technical, organizational, and human factors. This study aimed to explore the main challenges hindering the implementation of e-exams and analyze the potential role of blockchain technology in enhancing security and reliability. A descriptive methodology was employed, with data collected through a questionnaire distributed to faculty members. Results revealed that the most significant barriers included weak ICT infrastructure, a lack of administrative and technical support, and the absence of reliable and user-friendly e-exam systems. Additional challenges included unclear policies, a lack of awareness of the benefits of e-exams, and concerns about cheating and technical glitches. On the other hand, individual factors, such as resistance to change and the difficulty of designing e-exams, showed a relatively smaller impact. The findings highlight the need for stronger infrastructure, ongoing training, and clear institutional policies as prerequisites for the successful adoption of e-exams. Furthermore, the integration of blockchain technology offers a promising solution by ensuring consistent exam records, secure student identity verification, and transparent assessment processes. The study concludes that developing more reliable and effective e-assessment systems in Libya requires collaboration between technical and Libyan educational institutions, with blockchain technology considered a strategic option for enhancing trust and security in higher education.